A Real Saline Challenge: Diagnosing Primary Aldosteronism in the Setting of Chronic Kidney Disease - Sasan Mirfakhraee MD; Maria Rodriguez BS; Niloofar Ganji BS; Richard J. Auchus MD, PhD; Oksana Hamidi DO (SAGE Publishing, 2021)
Primary aldosteronism (PA) is the most common cause of secondary hypertension but remains largely undiagnosed. Chronic kidney disease (CKD) complicates the diagnosis of PA by affecting the biochemical screening evaluation and confirmatory testing, and by increasing the complication rate of adrenal venous sampling (AVS). To raise clinician awareness of the challenges of PA diagnosis in CKD, we present an illustrative case with subsequent review of the literature and discuss some recent developments in PA diagnostic strategies particularly applicable to the CKD population. A 67-year-old man with stage IIIb CKD was suspected of having PA due to treatment with 6 antihypertensive agents and the presence of intermittent hypokalemia. He had a positive biochemical screen for PA, and AVS demonstrated unilateral aldosterone excess. Subsequently, unilateral adrenalectomy resolved his PA, eliminating the patient's hypokalemia and improving his blood pressure. A MEDLINE literature search revealed 10 studies totaling 11 cases (including our own) of PA diagnosed in the setting of CKD. For each case, the clinical presentation, biochemical data, results of cross-sectional imaging, AVS details, and clinical response to surgery or medical therapy were characterized. The optimal strategy for the diagnosis and management of PA patients with CKD is not known. Although CKD patients often receive screening and subtype testing for PA similar to non-CKD patients, there are challenges in the interpretation of these tests. Novel strategies may include less invasive subtype testing or empiric treatment with mineralocorticoid receptor antagonists but additional studies are necessary.